2002
DOI: 10.1038/sj.onc.1205145
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc initiates illegitimate replication of the ribonucleotide reductase R2 gene

Abstract: The mechanisms through which the oncoprotein c-Myc initiates locus-speci®c gene ampli®cation are not understood. When analysing the initiation mechanism of cMyc-dependent ampli®cation of the mouse ribonucleotide reductase R2 (R2) gene, we observe c-Myc-dependent initiation of illegitimate DNA replication of the R2 gene. We demonstrate multiple simultaneous c-Myc-induced R2 replication forks, whereas R2 normally replicates with a single fork. In contrast, cyclin C replicates with only a single replication fork … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 49 publications
3
32
0
Order By: Relevance
“…This function has been recently found to play a prominent role in the tumor suppressor activity of p53 in vivo (Liu et al, 2004). Also, it is becoming increasingly clear that one consequence of deregulated MYC expression is genomic instability, which results in unscheduled DNA replication, gene rearrangements and chromosomal aberrations (Li and Dang, 1999;Kuschak et al, 2002;Sheen and Dickson, 2002;Karlsson et al, 2003). Thus, our data also support the hypothesis that deregulated MYC contributes to genomic instability in cells arrested by wild-type conformation p53.…”
Section: Myc and P53 Antagonism: Implications In Tumorigenesissupporting
confidence: 78%
“…This function has been recently found to play a prominent role in the tumor suppressor activity of p53 in vivo (Liu et al, 2004). Also, it is becoming increasingly clear that one consequence of deregulated MYC expression is genomic instability, which results in unscheduled DNA replication, gene rearrangements and chromosomal aberrations (Li and Dang, 1999;Kuschak et al, 2002;Sheen and Dickson, 2002;Karlsson et al, 2003). Thus, our data also support the hypothesis that deregulated MYC contributes to genomic instability in cells arrested by wild-type conformation p53.…”
Section: Myc and P53 Antagonism: Implications In Tumorigenesissupporting
confidence: 78%
“…MYC acted as an illegitimate replication-licensing factor. We concluded at this time that the types of R2 amplification observed as a result of MYC deregulation were in agreement with replication-driven instability (Kuschak et al , 2002. Other genes that undergo MYC-dependent gene amplification, such as Cyclin D2 and DHFR, also follow a replication-dependent mechanism (SF Louis and S Mai, unpubl.…”
Section: Myc and Genomic Instabilitymentioning
confidence: 48%
“…Work by our group next showed that MYC was able to promote illegitimate DNA replication resulting in more than one replication firing per origin per cell cycle (Kuschak et al 2002). Interestingly, in diploid synchronized PreB mouse lymphocytes, after a single pulse of conditional MYC deregulation, the R2 gene was replicated more than once in early S phase (Kuschak et al 2002).…”
Section: Myc and Genomic Instabilitymentioning
confidence: 99%
See 2 more Smart Citations